Development of Digital Worksheets Assisted by GeoGebra on Linear Function Material to Support Students Computational Thinking Skills - Putriani, Jesika Dwi; Hapizah, Hapizah; Mulyono, Budi (JME (Journal of Mathematics Education), 2025)
This study aims to develop a valid and practical digital worksheet in GeoGebra on linear functions, with a focus on the dangers of waste, to support students' computational thinking skills. This study uses a development studies design research method, consisting of three stages: preliminary research, development or prototyping phase, and assessment phase. The validation stage was conducted by three mathematics education lecturers and one mathematics teacher, with expert review, to assess content, construction, language, and technology. Meanwhile, practicality was evaluated by student responses during the small-group stage after using the digital worksheet in learning. The results showed that the digital worksheet using GeoGebra had an average validity of 93.81% (very valid) and practicality of 82.18% (practical). Thus, the developed digital worksheet using GeoGebra was declared valid and practical for use in mathematics learning and has the potential to improve students' computational thinking skills through solving contextual problems related to the dangers of waste.